PENGARUH PEMBERIAN IMUNOSTIMULAN DENGAN DOSIS BERBEDA TERHADAP PERTUMBUHAN IKAN KAKAP PUTIH (Lates calcarifer) - Ivandari, Intan Ria; Linayati, Linayati; Mardiana, Tri Yusufi (JURNAL LITBANG KOTA PEKALONGAN, 2019)
The objectives for this research are to know the effects of immunostimulants and optimal doses to increase the growth of white snapper fish. This research was conducted from August 25, 2018 until September 27, 2018 in the Laboratory of Brackish Water at the Fisheries Faculty of Pekalongan University. The methods used was the Completely Randomized Design Method consisting of 4 treatments and 3 replications. The given is artificial feed which mixed with differents doses of imunostimulant, treatment consist of A (0 ml/kg feed), Treatment B (5 ml/kg feed), Treatment C (10 ml/kg feed) and Treatment D (15 ml/kg feed). The seeds of white snapper fish are used for this research with size 4-5 cm and the density of 1 fish per liter. The parameters observed were biom ass growth, daily specific growth rate (%), ratio of the amount of feed needed, efficiency of feed utilization (%), degree of life (%) and the water quality as supporting data. The research results showed that the given immunostimulant on the feed had an effects on the growth of white snapper fish, Calculated F (13,474) > F Table 5% (4,066) and the F Table 1% (7,591). The use of immunostimulant give the highest results on the biomass growth of white snapper fish on the Treatment D of 9,13 gram, FCR 0,92, EPP 42.86 %, SGR 3,31 %, and SR 100%. The water quality during the research showed that the temperature range from 28 - 30 C, pH range is 7.0 – 7,4, Dissolved Oxygen range is 5.2 – 7.2 ppm, Salinity range is 32 – 35 ppt and Ammoniac range is 0.1 – 0.3 ppm. Keywords: White snapper fish seeds, Immunostimulants, Growth